How parents provide support for their children's learning in mobile ECCE context: practitioners' view - Mofokeng, Mahudi; Selepe, Mmakgabo Angelinah; Okeke, Chinedu (Institut Agama Islam Persis Bandung, 2025)
The study's primary aim was to explore the practitioner's views on the support parents provide for their children's learning in a mobile ECCE context to promote quality service delivery. The study was theoretically anchored by Epstein's overlapping spheres of influence theory. The researchers adopted the interpretive research paradigm combined with phenomenological research design to make sense of practitioners' objectivity. Qualitative data was obtained from semi-structured in-depth interviews by selecting and engaging twenty conveniently sampled ECCE practitioners. By adhering to the interview guide, the researcher's focused on the study's objectives to elicit rich data. The collected data was analysed thermatically using the Atlas. ti software. Findings revealed that parents support practitioner's through their involvement in decision-making process, regular attendance at the meetings, and in the cleaning of mobile units. In addition, parental support was in the form of assisting children to learn at the mobile units, and with homeworks. Parents also provided support by participating in fundraising drives and donation. It was recommended that better parental support and increased stakeholder interest in children's early learning will result in children's enhanced early cognitive development for future success.